2000
DOI: 10.1159/000051940
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Portal Hemodynamic Effects of Endoscopic Embolization for Esophageal Varices

Abstract: Background/Aim: Endoscopic embolization (EE) is a specialized treatment that obliterates esophageal varices along with their associated blood supply. The purpose of this study was to investigate the short-term effects of EE for esophageal varices on portal hemodynamics and liver function. Methods: Thirty patients with esophageal varices were included in this study. The portal blood flow was measured by an ultrasonic duplex Doppler system before and after EE. EE was performed by freehand intravariceal injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 17 publications
(17 reference statements)
1
32
0
Order By: Relevance
“…A similar association between the two has been reported by other workers [8, 19]. However, Chikamori et al [23]on the other hand did not find endoscopic embolization for oesophageal varices to produce any significant effect on the portal blood flow. They however did not study the gastric mucosal blood flow in particular.…”
Section: Discussionsupporting
confidence: 83%
“…A similar association between the two has been reported by other workers [8, 19]. However, Chikamori et al [23]on the other hand did not find endoscopic embolization for oesophageal varices to produce any significant effect on the portal blood flow. They however did not study the gastric mucosal blood flow in particular.…”
Section: Discussionsupporting
confidence: 83%
“…PSE decreases splenic blood flow, splenic venous pressure, and portal venous pressure [26][27][28] . Additionally, in a trial of 7 patients with cirrhosis and hepatocellular carcinoma treated with a combination of transcatheter hepatic arterial embolization and PSE, Han et al [29] demonstrated a significant decrease in portal venous pressures following therapy.…”
Section: Portal Hypertension and Associated Sequelaementioning
confidence: 98%
“…Additionally, in a trial of 7 patients with cirrhosis and hepatocellular carcinoma treated with a combination of transcatheter hepatic arterial embolization and PSE, Han et al [29] demonstrated a significant decrease in portal venous pressures following therapy. Interestingly, however, most studies which explored the hemodynamic effects of PSE did not demonstrate improvements in portal blood volume [26][27][28] . Portal venous hypertension is associated with numerous clinical manifestations.…”
Section: Portal Hypertension and Associated Sequelaementioning
confidence: 99%
“…In our patient the injection of both coils and ethanolamine oleate effectively maintained complete obstruction of a portal–systemic venous shunt, and furthermore liver function has been improved for 4 years. The mechanism of eradication of splenorenal shunt by percutaneous transretroperitoneal obliteration is the same as that of endoscopic injection sclerotherapy 14 or transjugular retrograde obliteration for the esophagogastric varices 15 . 5% EOI has the ability to damage the endothelial cells and produce thrombi when it is injected in a controlled way.…”
Section: Discussionmentioning
confidence: 99%